UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN PTK MELALUI BIMLAT KOMUNIKASI DARING WAG GURU PNS MADRASAH IBDITIDAIYAH SWASTA BINAAN DI KEMENAG KOTA SERANG - JUARIAH JUARIAH; ALVIA QURONITA AYUNINISAI SHOLIHAH; SUPARDI UK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Guidance and training activities through online communication are further strengthened by the enactment of President Number 7 of 2020 concerning the Task Force for the Acceleration of Handling Corona Virus Disease 2019 and Minister of Health Regulation Number 9 Year 2020 concerning Guidelines for Large-Scale Social Restrictions (PSBB). In the Context of Accelerating Handling of Corona Virus Disease 2019 State Gazette of the Republic of Indonesia of 2020 Number 326, stipulates Large-Scale Social Restrictions (PSBB) in the Serang Region of Banten Province in the Context of Accelerating Handling of Corona Virus Disease 2019, thus further making it clear that Civil Servants (PNS) required to work from home in exchange for daily performance as a monthly report to be reported to the relevant agency where the PNS teacher works is known as work from home (work form home), then the implementation of guidance exercises for the period April 6 to April 30 2020 for PNS assisted teachers, become one of the solutions to help work from home (WFH: work form home) in the Region of the Ministry of Religion, Tangerang Regency. This type of research is Supervision Action Research (PTKp), in which supervisors provide guidance and training in preparing PTK to participants online by applying direct instruction strategies in Cycle I and then in Cycle II mastery learning strategies. Based on this study, it was concluded that there was a linear relationship between the participants' activeness in participating in Bimlat activities and competence in preparing PTK to achieve graduation with an